PERANCANGAN DAN PEMBUATAN MESIN PENCETAK BRIKET DENGAN MENGGUNAKAN SCREW CONVEYOR DENGAN KOMPOSISI ARANG BATOK KELAPA, SERBUK KAYU MAHONI DAN PEREKAT TEPUNG TAPIOKA - Muhammad Luthfi; Yusup Nur Rohmat; Delffika Canra; Febri Yani (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Indramayu is a city that has a large agricultural and plantation sector. However, the waste from agricultural and plantation products is still not optimal to be reprocessed such as waste coconut shells, sawdust, and pieces of wood from the rest of furniture making. So, the purpose of this study is to determine the design, product results and performance of a briquette charcoal printing machine from the utilization of coconut shell charcoal waste and mahogany sawdust which is matrices using tapioca starch adhesive. The method used starts from designing, making tools, to testing the performance of the tool. From the results of the research that has been done, a briquette molding machine is obtained that utilizes motor rotation to move the screw conveyor from the rotating shaft. The design that has been made has dimensions of 600mm x 500mm x 700mm. The briquette molding machine is driven using a 0.75 Hp electric motor and produces a maximum moment on the frame of 7,139.7 N.mm with a main frame safety factor of 1.4. In addition, the test results show that the greater the mass of coconut shell charcoal, the less water content. Meanwhile, the longer the drying time of the briquettes, the longer the ember flame time, while the ash content is getting less